The Relevance of Bijinesu Nihongo Course to The Cultural Understanding of Students Participating in The Internship to Japan - Amalia, Aan; Rahardjo, Hardianto (IZUMI, 2022)
Along with the Japanese population drop, the number of productive age workforce in Japan also decreasing constantly. This situation drove Japan to welcome younger workforces and professionals from other countries. While some of the younger workforces aims at a more permanent employment, some of them are only temporary workers and interns. Among those whose going through internship programs are students from Widyatama University Indonesia. One of the hardships the students must went through is adapting with new culture and work ethics. While Widyatama University have tried to prepare the students for their internship period in Japan through various methods, one of them is through the “Bijinesu Nihongo” class. This research is condoned in the interest of finding out how effective the “Bijinesu Nihongo” syllabus is in real life internship period according to the students who have already or currently undergoing internship in Japan. Using descriptive qualitative methods, internship students would act as research subject, and be interviewed about their working experiences in Japan. The interview results will indicate how much of the subject they learned in class is truly relevant during their internship period. The result would greatly assist coursers to revise and update better curriculum to better prepare students facing their internship. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor